Low-Molecular-Weight Heparin Versus Aspirin in Early Management of Acute Ischemic Stroke: A Systematic Review and Meta-Analysis - Xia, Hui; Wang, Ziyao; Tian, Min; Liu, Zunjing; Zhou, Zhenhua (Frontiers in Immunology, 2022)
Objectives: To evaluate the difference between low-molecular-weight heparin (LMWH) and aspirin in preventing early neurological deterioration (END) and recurrent ischemic stroke (RIS), post-recovery independence, and safety outcomes in acute ischemic stroke. Materials and Methods: We performed systematic searches of the PubMed, Embase, and Cochrane Library databases for full-text articles of randomized controlled trials (RCTs) of LMWH vs. aspirin in the early management of acute ischemic stroke. Information on study design, eligibility criteria, baseline information, and outcomes was extracted. Synthesized odds ratios (ORs) with 95% confidence intervals (CIs) are used to present the differences between the two treatments based on fixed-effects models. Results: Five RCTs were retrieved from the online databases. The results showed no significant difference in efficacy outcomes between the two groups among unselected patients. Subgroup analysis showed that LMWH was significantly related to a lower incidence of END events (odds ratio [OR]: 0.28, 95% confidence interval [CI]: 0.20–0.38) and reduced occurrence of RIS during treatment (OR: 0.34, 95% CI: 0.16–0.75) in non-cardioembolic stroke. LMWH significantly increased the number of patients with a modified Rankin scale (mRS) score of 0–1 at 6 months in patients with large-artery occlusive disease (LAOD) (OR: 1.02, 95% CI: 1.02 to 2.37). LMWH had a similar effect on symptomatic intracranial hemorrhage (sICH) and major extracranial hemorrhage during treatment to that of aspirin, except that LMWH was related to an increased likelihood of extracranial hemorrhage. Conclusions: In patients with acute non-cardioembolic ischemic stroke, especially that with large-artery stenosis, LMWH treatment significantly reduced the incidence of END and RIS, and improved the likelihood of independence (mRS 0–1) at 6 months compared with those with aspirin treatment. LMWH was related to an increased likelihood of extracranial hemorrhage among all patients; however, the difference in major extracranial hemorrhage and sICH was not significant.